Experiences in Reflective Action Research with Practice Teachers - José Federman Muñoz Giraldo; Josefina Quintero Corzo; Raúl Ancízar Munévar Molina (Universidad Autónoma de Baja California, 2002)
This article presents processes and results of experiments conducted by a group of teachers and students in teacher-training programs at the University of Caldas (Colombia). The purpose of the article is to present the results of a consultancy process for educators in training during their practice teaching in public schools, using cycles of reflective action research. Participation, collaborative work, decision-making and critical reflection of the action are evidences that allow showing how a teacher in training learns to do research while learning to teach.